PENGARUH MARKETING MIX DAN SYARIAH COMPLIANCE TERHADAP KEPUTUSAN NASABAH MEMILIH BANK UMUM SYARIAH DI KUDUS (Equilibrium: Jurnal Ekonomi Syariah, 2016)
This study aimed to examine the influence of mix marketing and sharia compliance on customer’s decision in choosing Sharia bank in Kudus. It used purposive sampling method with 120 respondents. Hypothesis testing used multiple linear regression analysis. The analysis of T test showed that product influences the customer’s decision because thitung > ttable (2,239> 1,657), Price influences the customer’s decision because tcount > ttable (2,563> 1, 657). Place influences the customer’s decision because tcount > ttable (2,002> 1, 657). Promotion influences the  customer’s  decision  because  tcount  >  ttable  (4.436>  1,657). Syariah compliance influences the customer’s decision because tcount > ttable (2,072> 1, 657). Based on F test, it indicated that Fcount > Ftable (11 689> 2.290) which means the mix marketing consists of product, price, place, promotion and Sharia compliance significantly influenced the customers’ decision in choosing sharia banks in Kudus.